Assessing the Impact of Land Cover, Soil, and Climate on the Storage Potential of Dryland Sand Dams - Eisma, Jessica A.; Saksena, Siddharth; Merwade, Venkatesh (Frontiers in Water, 2021)
Sand dams, a water-harvesting structure employed by rural communities in drylands have an inconsistent record of effectiveness. While many sand dams are highly functioning, improper siting, siltation, seepage, and high rates of evaporation from shallow sand reservoirs inhibit the water storage capacity of some sand dams. This study examines large-scale drivers of sand dam storage potential through analysis of an integrated surface and subsurface flow model. Multiple simulations were run, and comparative simulation analyses consider the effect of geomorphological factors, intraseasonal rainfall variability, and future climate conditions on sand dam performance criteria. The analyses revealed that a watershed highly cultivated with low water crops actually reduces evapotranspiration below that of natural vegetation and supports higher groundwater recharge. Additionally, intraseasonal variation and volume of rainfall impact sand dam performance less than the prevailing pattern and duration of dry and rainy seasons. Sand dams constructed in watersheds with sandier soils may experience greater connectivity with the stream margins and thus provide additional groundwater recharge. Lastly, climate change may improve some conditions desirable for sand dam performance, such as extending the duration of the rainy season and reducing overall evapotranspiration. However, the interactions between the expected climate change conditions and other geomorphological factors may result in a net decline in sand dam performance. The results of this study may help identify watersheds that are likely to support a sand dam with high potential for capturing and storing water throughout the dry season.